Kajian Stilistika Sastra Lisan Tembang Asal Sanga Desa Kabupaten Musi Banyuasin - Permana, Andi; Hetilaniar, Hetilaniar; Agustin, Juaidah (Indonesian Research Journal on Education, 2023)
The problem in this research is how to study the stylistics of the oral literature of Tembang fromSangaDesa, MusiBanyuasin Regency based on figurative language and imagery. The purpose of this study was to identify and describe figurative language and imagery in the study of Tembangstylistics from Sanga Village, Musi Banyuasin Regency. The method used is descriptive qualitative method. The source of data in this study is video recording from YouTube. The videos that will be analyzed are 3 videos of Tembang chanting, namely Tembang from SangaDesa sung by a young woman from SangaDesa (SMAN1 SanDes Channel) July 2020 edition, Tembang sung by parents/artists of Tembang from Ngulak, SangaDesaSubdistrict (ImahNurdin ) April 2017 edition and a song sung by a Tembang artist from Ngulak, Sanga Desa Subdistrict (Budaya Muba) May 2021 edition. The results of the research on the stylistic study of Tembang from Sanga Desa, Musi Banyuasin Regency, obtained 10 language styles and 5 imagery which has 4 lines in each stanzas. The language style studied consisted of simile, metaphor, ellipsis, repetition, litotes, hyperbole, personification, irony, association and cynicism while the imagery consisted of visual, auditory, motion, smell and taste images.